A comparison of emotional wellbeing and burnout of primary care professionals in 2014 and 2021 - Abad, Alejandro; Fuentes, Araceli; Paredes, Eugeni; Godoy, Sofia; Perera, Sara; Yuguero, Oriol (Frontiers in Public Health, 2023)
Background Due to the pandemic that started in February-March 2020 and after many years of economic restrictions suffered by our health system, the levels of stress, exhaustion and suffering among health workers has increased. Objective Our study aims to perform a comparative analysis of the degree of burnout and emotional wellbeing among health professionals between 2014 and 2021. Methods This is a comparative descriptive study of two cohorts of primary care professionals of the Lleida health region (SPAIN). We have one cohort from 2014 and another from 2021 with the same selection criteria. Burnout was assessed using the Maslach Burnout Inventory (MBI-HSS) test. Gender, age, professional category and work environment were also evaluated. Results We obtained a response rate in 2014 of 52.7% (n=267) and of 41.4% (n=217) in 2021 with similar sociodemographic characteristics. There are significant differences (p<0.001) in the three categories of burnout. The high scores for emotional exhaustion and depersonalization have increased, rising between 2014 and 2021 from 23.2 to 60.8% and from 12.4 to 42.4%, respectively. However, there is also a significant increase in high personal accomplishment, rising from 9.0 % in 2014 to 26.7%. We have also detected differences depending on age and professional role. Conclusion This study shows worsening burnout levels of primary care professionals in our region, specifically emotional exhaustion and depersonalization. However, it also shows that during the pandemic, personal accomplishment was reinforced.